Cripto‐1 Expression in Glioblastoma Multiforme. (28th March 2014) - Pilgaard, Linda; Mortensen, Joachim Høg; Henriksen, Michael; Olesen, Pia; Sørensen, Preben; Laursen, Rene; Vyberg, Mogens; Agger, Ralf; Zachar, Vladimir; Moos, Torben; Duroux, Meg
Abstract Human glioblastoma multiforme (GBM) is an aggressive cancer with a very poor prognosis. Cripto‐1 (CR‐1) has a key regulatory role in embryogenesis, while in adult tissue re‐expression of CR‐1 has been correlated to malignant progression in solid cancers of non‐neuronal origin. As CR‐1 expression has yet to be described in cerebral cancer and CR‐1 is regulated by signaling pathways dysregulated in GBM, we aimed to investigate CR‐1 in the context of expression in GBM. The study was performed using enzyme‐linked immunosorbent assay (ELISA), Western blotting, polymerase chain reaction (PCR) and immunohistochemistry to analyze the blood and tissue from 28 GBM and 4 low‐grade glioma patients. Within the patient cohort, we found high CR‐1 protein levels in blood plasma to significantly correlate with a shorter overall survival. We identified CR‐1 in different areas of GBM tissue, including perivascular tumor cells, and in endothelial cells. Collectively, our data suggest that CR‐1 could be a prognostic biomarker for GBM with the potential of being a therapeutic target.